PPARγ Agonists Attenuate Palmitate-Induced ER Stress through Up-Regulation of SCD-1 in Macrophages - Ikeda, Jiro (PLoS One, 2015)
BACKGROUND: Clinical trials have shown that treatment of patients with type 2 diabetes with pioglitazone, a peroxisome proliferator-activated receptor (PPAR)γ agonist, reduces cardiovascular events. However, the effect of PPARγ agonists on endoplasmic reticulum (ER) stress that plays an important role in the progression of atherosclerosis has not been determined. We sought to determine the effect of PPARγ agonists on ER stress induced by palmitate, the most abundant saturated fatty acid in the serum. METHODS AND RESULTS: Protein expression of ER stress marker was evaluated by Western blot analysis and stearoyl-CoA desaturase1 (SCD-1) mRNA expression was evaluated by qRT-PCR. Macrophage apoptosis was detected by flowcytometry. Pioglitazone and rosiglitazone reduced palmitate-induced phosphorylation of PERK, a marker of ER stress, in RAW264.7, a murine macrophage cell line. Pioglitazone also suppressed palmitate-induced apoptosis in association with inhibition of CHOP expression, JNK phosphorylation and cleavage of caspase-3. These effects of pioglitazone were reversed by GW9662, a PPARγ antagonist, indicating that PPARγ is involved in this process. PPARγ agonists increased expression of SCD-1 that introduces a double bond on the acyl chain of long-chain fatty acid. 4-(2-Chlorophenoxy)-N-(3-(3-methylcarbamoyl)phenyl)piperidine-1-carboxamide, an inhibitor of SCD-1, abolished the anti-ER stress and anti-apoptotic effects of pioglitazone. These results suggest that PPARγ agonists attenuate palmitate-induced ER stress and apoptosis through SCD-1 induction. Up-regulation of SCD-1 may contribute to the reduction of cardiovascular events by treatment with PPARγ agonists.